THE GAMIFICATION OF REHABILITATION: A NARRATIVE REVIEW OF SOCIAL AND BEHAVIORAL IMPACTS - Ożga, Sebastian; Wąs, Lukasz; Pilarek, Marcel; Tryczyński, Piotr; Laskowska, Wiktoria; Kwolek, Klaudia; Janczarski, Szymon; Roszkowska, Monika; Furtak, Michał; Sarna, Dominika (International Journal of Innovative Technologies in Social Science, 2026)
Objectives: This narrative review aims to critically examine gamified rehabilitation as a socio-technical phenomenon. It evaluates clinical effectiveness, analyzes underlying behavioral and motivational mechanisms, explores social implications-including equity, digital inclusion, and social connectivity-and assesses the regulatory and governance challenges associated with implementing digital health technologies in clinical and home-based settings.Methods: Adopting a concept-driven framework and a socio-technical perspective, this study synthesized peer-reviewed research identified through PubMed, Scopus, and Web of Science. The review focuses on virtual reality (VR) and "exergames" applied to orthopaedic, neurological, and chronic conditions. Information was extracted regarding clinical metrics, psychological indicators grounded in Self-Determination Theory (SDT), and systemic impacts on healthcare delivery.Findings: The review indicates that gamified interventions are clinically effective, particularly for improving balance in neurorehabilitation, while significantly enhancing patient engagement and adherence. Success is driven by satisfying core psychological needs for autonomy, competence, and relatedness, often facilitated by AI-driven adaptive difficulty to induce "flow" states. However, the "digital divide" remains a critical barrier, potentially exacerbating health inequalities. Identified risks include behavioral dysregulation, system dependency, and ethical concerns regarding "black-box" algorithms and data privacy. Economically, these systems support health system sustainability through decentralized, asynchronous care models that reduce personnel costs.Conclusions: Gamification represents a transformative shift toward decentralized, home-based rehabilitation. While enhancing adherence through neurobiological reinforcement, its long-term success requires a socio-technical approach that aligns technical architecture with users' cultural and environmental contexts. Future integration must prioritize inclusive design, modernized reimbursement structures, and robust regulatory compliance to ensure equitable access.